EKSPRESI PUITIK DALAM ANTOLOGI PUISI DWIBAHASA M.AAN MANSYUR: KAJIAN TERJEMAHAN PUISI - I Gusti Agung Sri Rwa Jayantini; Ronald Umbas; Ni Komang Arie Suwastini; Putu Desi Anggerina Hikmaharyanti (Universitas Muhammadiyah Surakarta, 2022)
Poetic expression in poetry of different languages is an interesting study because this literary work reflects not only the personal expression of the poet but also the world through diction and figurative language that carry certain moral messages. This study aims to reveal the translation of comparative and contradictory figurative languages which are used to convey poetic expressions found in the poems about love and the existence of a poem, which are understood by the poet, M.Aan Mansyur, in his bilingual poetry collection,